Object matching and recognition under semi-affine transformation and occlusion - Thio, Hwee Li. (2008)
In this thesis, a method is proposed to extract features from an object for matching and recognition under simple transformations and occlusion. The feature proposed comprises of both local and global characteristics. The idea is to combine both features, to make the proposed method less sensitive to noise and occlusion.